Rapid Transformation of Ferulic Acid to 4-Vinyl Guaiacol by Bacillus pumilus S-1 - Hua, Dong-Liang; Liang, Xiao-Hui; Zhang, Xiao-Dong; Zhang, Jie; Xu, Hai-Peng; Li, Yan; Xu, Ping (Asian Journal of Chemistry, 2012)
A Bacillus pumilus strain S-1, earlier reported to efficient in converting of isoeugenol to vanillin, was found to have the biotransformation ability of ferulic acid. This strain rapidly dissimilated 1 g L-1 ferulic acid within 3 h and 4-vinyl guaiacol was identified as the main product. The highest concentration of 4-vinyl guaiacol, 0.72 g L-1, was obtained with a molar yield of 93.1 %. Different from former reports, 4-vinyl guaiacol was not further metabolized and no other vanilla flavour compounds were found.